Ash Composition in the Combustion of Promising Slurry Fuels; Coke and Chemistry; Vol. 63, iss. 3 - Nyashina G. S. Galina Sergeevna; Kurgankina M. A. Margarita Aleksandrovna; Akhmetshin M. R. Mark Rustamovich; Medvedev V. V. Valery Vasilievich (2020, 2020)
Title screen